Development of an Aquabalance Android Application for Real-Time Monitoring ofWater Temperature and pH in Greenhouses - Mochammad Rifki Ulil Albaab; Slamet, Ahmad Haris Hasanuddin; Sekar Ayu Wulandari; Septine Brillyantina; Muhammad Haris Suhud; Rasyidah Aisy Ariyanto (Kadiri University - Faculty of Agriculture, 2025)
The rapid development of technology has significantly impacted the agricultural sector, particularly in optimising farming activities in restricted spaces like greenhouses. Monitoring environmental parameters such as water temperature and pH is crucial for successful plant cultivation. This research aims to develop an Android application, Aquabalance, for real-time monitoring of water temperature and pH levels in a greenhouse to improve efficiency and minimise the need for manual monitoring. The system integrates Arduino UNO, ESP8266, DHT22 temperature sensor, and a water pH sensor, achieving accuracy levels of ±0.5°C for temperature and ±0.1 pH for water. The development process utilised the Scrum method, ensuring flexibility and user-centric design. Testing was conducted with two participants—a farmer and a researcher—who assessed key functionalities such as registration, login, and data retrieval. The Android application performed with a 95% success rate, with an average response time of 2–3 seconds for real-time data display. User satisfaction was evaluated on a 1-5 scale, with an average score of 4.7 for usability, navigation, and performance. The results indicate that Aquabalance effectively facilitates greenhouse monitoring, providing real-time, remote access to essential environmental data, ultimately enhancing greenhouse management and reducing time spent on manual monitoring tasks.